Extreme downside risk in asset returns - Lerby M. Ergun (Bank of Canada, 2019)
Does extreme downside risk require a risk premium in the pricing of individual assets? Extreme downside risk is a conditional measure for the co-movement of individual stocks with the market, given that the state of the world is extremely bad. This measure, derived from statistical extreme value theory, is non-parametric. Extreme down-side risk is used in double-sorted portfolios, where I control for the five Fama-French and various non-linear asset pricing factors. I find that the average annual excess return between high- and lowexposure stocks is around 3.5%.
Keywords: C14; G12; G11; 330; Asset pricing; Econometric and statistical methods